ANALISIS KINERJA KEUANGAN PADA PERUSAHAAN PERHOTELAN SEBELUM DAN SAAT PANDEMI COVID-19 - Syarifa Annisah Ingkari Muhammad Zen (2022)
This study's purpose to analyze the differences in the financial performance of Hospitality Companies before and during Covid-19 pandemic. This study uses four variables which consists of liquidity (CR), solvency (DER), profitability (ROE), and activity (TATO). The population in this study are hotel companies who listed on the Indonesia Stock Exchange in 2018-2021. Sample selection method used in this research is purposive sampling in which 14 companies were included in the hospitality companies as sample. The data analysis technique used in this study was the paired sample t-test and the Wilcoxon signed rank test using the SPSS 25. The results of this study indicate that the liquidity and solvency variables before and during the Covid-19 pandemic were not different, while for the profitability variable and activities before and during the Covid-19 pandemic were different.